Boosting K-ion kinetics by interfacial polarization induced by amorphous MoO3-x for MoSe2/MoO3-x@rGO composites. (10th July 2022) - Yang, Jiangshao; Liu, Liwen; Wang, Daoyi; Tao, Jianming; Yang, Yanming; Li, Jiaxin; Lin, Yingbin; Huang, Zhigao
Research highlights: Ø The K-ion storage of MoSe2 @rGO is enhanced by incorporating amorphous MoO3- x with oxygen vacancies. Ø A built-in electric field benefits for electron-transfer and K-ion migration across the hetero-junction interface. Ø Larger dielectric polarization induced by MoO3- x reduces charge transfer resistance and enhance K-ion migration across electric double-layer. Abstract: Promoting interfacial reaction kinetics is highly desirable for achieving high-performances of anode material in alkali-ion batteries. Herein, flower-like MoSe2 /MoO3- x @rGO composites are fabricated by a facile solvothermal method involving a thermal-treatment at 800°C. When evaluated as an anode material for potassium ion batteries, MoSe2 /MoO3- x @rGO delivers 248.2 mA h g −1 after 50 cycles at 0.2 A g −1 with a capacity retention of 84.6% and 182.9 mA h g −1 after 150 cycles at 1.0 A g −1 with a capacity retention of almost 61.2%, superior to those of bare MoSe2 or MoSe2 @rGO composites. Analysis from electrochemical measurements, the amorphous MoO3- x containing oxygen vacancies could not only effectively buffer the self-aggregation of MoSe2 nanosheets but also provides lots of accessible active sites for potassium ion storage. Additionally, the open channels in the amorphous MoO3- x phase lead to easier ion hopping and smaller diffusion barriers. Furthermore, the built-in electric field at the interface would be beneficial for electron transfer and K-ion migration across the hetero-junction interface. Moreover, larger dielectric polarization induced by the high relative permittivity of amorphous MoO3- x would reduce charge transfer resistance and enhance K-ion migration across electric double-layer. Our work provides new insight into the enhanced performance of anode material coated by an amorphous layer with large relative permittivity. Graphical abstract: Image, graphical abstract